Biogeography of American Northwest Hot Spring A/B′-Lineage Synechococcus Populations - Becraft, Eric D.; Wood, Jason M.; Cohan, Frederick M.; Ward, David M. (Frontiers in Microbiology, 2020)
Island biogeography studies of unicellular cyanobacteria inhabiting hot springs have begun to challenge the notion that “everything is everywhere and nature selects.” However, detailed analyses of how diversity is patterned relative to physical separation and physiochemical differences among springs, especially at local to regional scales, have been limited by the low resolution provided by the molecular markers studied. We analyzed large datasets obtained by high-throughput sequencing of a segment of the photosynthesis gene psaA from samples collected in hot springs from geothermal basins in Yellowstone National Park, Montana, and Oregon, all known from previous studies to contain populations of A/Bʹ-lineage Synechococcus. The fraction of identical sequences was maximal (0-21%) among springs separated by <50 km, while springs separated by 50 km to 110 km rarely shared (0-6%) sequence variants and springs separated by >800 km shared sequence variants extremely rarely (<1%). Phylogenetic analyses provided evidence for endemic lineages that could be related to geographic isolation and/or geochemical differences on regional scales. Ecotype Simulation 2 was used to predict putative ecotypes and their membership and canonical correspondence analysis was used to examine the geographical and geochemical bases for variation in their distribution. Across the range of Oregon and Yellowstone, geographical separation explained the largest percentage of the differences in distribution of ecotypes (9.5% correlated to longitude; 9.4% latitude), with geochemical differences explaining the largest percentage of the remaining differences in distribution (9.3%-7.4% correlated to magnesium, sulfate, and sulfide). However, among samples in the Greater Yellowstone Ecosystem, geochemical differences significantly explained the distribution of ecotypes (6.5%-9.3% correlated to magnesium, boron, sulfate, silicon dioxide, chloride, and pH). Nevertheless, differences in the abundance and membership of ecotypes in Yellowstone springs with similar chemistry suggested that allopatry may be involved even at local scales. Synechococcus populations have diverged both by physical isolation and physiochemical differences, and populations on surprisingly local scales have been evolving independently.